2009
DOI: 10.1371/journal.pbio.1000105
|View full text |Cite|
|
Sign up to set email alerts
|

Stress-Dependent Coordination of Transcriptome and Translatome in Yeast

Abstract: Cells rapidly alter gene expression in response to environmental stimuli such as nutrients, hormones, and drugs. During the imposed “remodeling” of gene expression, changes in the levels of particular mRNAs do not necessarily correlate with those of the encoded proteins, which could in part rely on the differential recruitment of mRNAs to translating ribosomes. To systematically address this issue, we have established an approach to rapidly access the translational status of each mRNA in the yeast Saccharomyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
145
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(156 citation statements)
references
References 69 publications
10
145
1
Order By: Relevance
“…Translatome and transcriptome in yeast are regulated conjointly in response to various stresses, such as amino acid depletion, osmotic shock, and sorbitol treatment (7). Thus the genes up-regulated at the level of transcription also yield more protein product as well, a process that is termed "potentiation."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Translatome and transcriptome in yeast are regulated conjointly in response to various stresses, such as amino acid depletion, osmotic shock, and sorbitol treatment (7). Thus the genes up-regulated at the level of transcription also yield more protein product as well, a process that is termed "potentiation."…”
Section: Discussionmentioning
confidence: 99%
“…However, they are designed for the quantification of individual proteins rather than for addressing the details of translation. Indirect approaches, such as comparative microarray profiling of mRNAs within monosomes and polysomes, are popular as well (5)(6)(7)(8). These methods enable estimation of the mRNA transcripts that are being translated.…”
mentioning
confidence: 99%
“…Stresses found to deplete bulk polysomes include the sudden withdrawal of glucose (Ashe et al 2000;Arribere et al 2011;Vaidyanathan et al 2014) or amino acids (Smirnova et al 2005); nutrient limitation that induces sporulation (Brar et al 2012); temperature shift (Preiss et al 2003); and the addition of cellular stress agents: hyperosmotic salt (Melamed et al 2008), hydrogen peroxide (Shenton et al 2006), fusel alcohols (Smirnova et al 2005), or drugs: rapamycin (Preiss et al 2003), calcofluor-white (Halbeisen and Gerber 2009), and chlorpromazine (Deloche et al 2004). These studies have shown that there is widespread reprogramming of translation following stress with diminished ribosome association of some mRNAs hypersensitive to stress, while the translation of other mRNAs is relatively resistant to the stress.…”
Section: Global Approaches To Studying Translation Controlsmentioning
confidence: 99%
“…The cell enters a program where resources are directed from rapid growth to stress protection. Components of ribosomes and gene products required for ribosomal biogenesis are strictly down-regulated on the levels of transcriptional initiation, translation, and mRNA turnover (Tang et al 2001;Grigull et al 2004;Halbeisen and Gerber 2009). On the other hand, mRNAs encoding proteins required for survival in stress conditions are stabilized and preferentially translated (Lü et al 2006;Halbeisen and Gerber 2009;Molin et al 2009;Powley et al 2009).…”
Section: Introductionmentioning
confidence: 99%